Решите уравнение : (х+1) (х+2) = (х-3) (х+4) (3 х-1) (2 х+7) - (х+1) (6 х-5) = 16 24 - (3 у+1) (4 у-5) = (11-6 у) (2 у-1) + 6 (6 у+2) (5-у) = 47 - (2 у-3) (3 у-1)

0
Ответы (1)
  1. 28 января, 14:28
    0
    1) (x + 1) * (x + 2) = (x - 3) * (x + 4);

    x^2 + 2x + x + 2 = x^2 + 4x - 3x - 12;

    x^2 - x^2 + 2x + x - 4x + 3x = - 12 - 2;

    3x - x = - 14;

    2x = - 14;

    x = - 14 : 2;

    x = - 7.

    2) (3x - 1) * (2x + 7) - (x + 1) * (6x - 5) = 16;

    6x^2 + 21x - 2x - 7 - 6x^2 + 5x - 6x + 5 = 16;

    19x - x = 16 + 7 - 5;

    18x = 18;

    x = 18 : 18;

    x = 1.

    3) 24 - (3y + 1) * (4y - 5) = (11 - 6y) * (2y - 1) + 6;

    24 - 12y^2 + 15y - 4y + 5 = 22y - 11 - 12y^2 + 6y + 6;

    -12y^2 + 12y^2 + 11y - 22y - 6y = - 5 - 24 - 5;

    -17y = - 34;

    y = - 34 : (-17);

    y = 2.

    4) (6y + 2) * (5 - y) = 47 - (2y - 3) * (3y - 1);

    30y - 6y^2 + 10 - 2y = 47 - 6y^2 + 2y + 9y - 3;

    30y - 6y^2 + 6y^2 - 2y - 2y - 9y = 47 - 3 - 10;

    17y = 34;

    y = 34 : 17;

    y = 2.
Знаешь ответ на этот вопрос?